Integrasi Manajemen Kepala Sekolah dan Nilai Kristiani dalam Mempertahankan Tenun Motif Buna di SMA Negeri Nunkolo - Serli Susanti Banunaek; Andrian Wirasyahputra; Hendrik A. E. Lao (International Forum of Researchers and Lecturers, 2024)
Local culture, including the practice of weaving Buna motifs, is a cultural heritage that needs to be preserved in the era of globalization which, if not maintained, could hinder the development of traditional practices. This research aims to determine the importance of combining management principles and Christian values ​​in maintaining the practice of weaving Buna motifs. This research used a qualitative approach involving the principal, teachers and students of Nunkolo State High School as participants. Data collection was carried out through unstructured interviews, observation and analysis of related documents. The research discussion was analyzed descriptively which showed the results that the school principal plays a very important role in the world of education with his leadership in developing educational programs that support the preservation of local culture, as well as exploring how the Christian values ​​adhered to by the school can provide a moral and ethical foundation in preserving cultural heritage. The school principal's management seeks to strengthen Christian values ​​through the practical activity of weaving Buna motifs as a means of forming cooperation between students and craftsmen which has an impact on student behavior which increasingly respects traditions that have been maintained for a long time.